2002
DOI: 10.1113/jphysiol.2001.013296
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of currents carried by HERG, with and without coexpression of MiRP1, and the native rapid delayed rectifier current. Is MiRP1 the missing link?

Abstract: Although it has been suggested that coexpression of minK related peptide (MiRP1) is required for reconstitution of native rapid delayed-rectifier current (I Kr ) by human ether-a-go-go related gene (HERG), currents resulting from HERG (I HERG ) and HERG plus MiRP1 expression have not been directly compared with native I Kr . We compared the pharmacological and selected biophysical properties of I HERG with and without MiRP1 coexpression in Chinese hamster ovary (CHO) cells with those of guinea-pig I Kr under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
120
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(131 citation statements)
references
References 27 publications
8
120
2
1
Order By: Relevance
“…As early as 1995, it was suggested that the KCNE1 protein (also known as MiRP1 or minK) is a subunit of I Kr channels based on experiments in which antisense KCNE1 oligonucleotides reduced I Kr current levels in AT1 cardiomyocyte-like cells (38). A subsequent report using HEK293 cells supported this idea by showing that KCNE1 alters hERG function (39), whereas another study using CHO cells did not (40). If KCNE1/minK participates as subunits or regulators of I Kr channels, it appears from our findings that it does so posttranslationally, perhaps as described for I Ks channels (41); alternatively, it may assemble from nonassociating transcripts, or in cell types other than the two examined here.…”
Section: Discussionsupporting
confidence: 51%
“…As early as 1995, it was suggested that the KCNE1 protein (also known as MiRP1 or minK) is a subunit of I Kr channels based on experiments in which antisense KCNE1 oligonucleotides reduced I Kr current levels in AT1 cardiomyocyte-like cells (38). A subsequent report using HEK293 cells supported this idea by showing that KCNE1 alters hERG function (39), whereas another study using CHO cells did not (40). If KCNE1/minK participates as subunits or regulators of I Kr channels, it appears from our findings that it does so posttranslationally, perhaps as described for I Ks channels (41); alternatively, it may assemble from nonassociating transcripts, or in cell types other than the two examined here.…”
Section: Discussionsupporting
confidence: 51%
“…Stably transfected CHO cells were cultured as previously described 9,10 and perfused with an external solution containing (in mmol/L): NaCl 130, KCl 4, CaCl 2 1, MgCl 2 1, HEPES 10, and glucose 10 (pH adjusted to 7.4 with NaOH). The internal solution contained (in mmol/L): K-aspartate 80, KCl 42, KH 2 PO 4 10, MgATP 5, phosphocreatine 3, HEPES 5, and EGTA 5 (pH adjusted to 7.2 with KOH).…”
Section: Methodsmentioning
confidence: 99%
“…KCNE2 (MiRP1) co-assembles with HERG (31,32), although the functional implications have been debated (33), and it has been difficult to demonstrate expression of KCNE2 in human heart (34). The KCNE2 polymorphism T8A, which abrogates complex glycosylation of KCNE2, mildly increases I Kr sensitivity to block by the antibiotic sulfamethoxazole (35).…”
Section: N-linked Glycosylation-induced Protection Of Herg Doesmentioning
confidence: 99%